(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
Politics is entirely active in the construction of relations between power and death and continuously takes action that determine how we die, who dies, when and for which reasons. Before and beyond Covid-19, political power appropriates death to make it an object of its management, determining the course of our lives. But how does dance politicize the relationships between life, power, body and death? Through which aesthetic procedures does dance approach a political body and transform the view of what life is and how to recognize it? Based on two scenes - one by the German cabaretist Valeska Gert, in her solo Death (1925), and another by the Brazilian choreographer Marcelo Evelin, Batucada (2014) - this article highlights some contributions of dance to the reflection of the social mechanisms that produce life and that recognize what makes a body alive.